Rational Fuzzy Cone Contractions on Fuzzy Cone Metric Spaces with an Application to Fredholm Integral Equations. (10th May 2021) - Rehman, Saif Ur; Aydi, Hassen
Abstract : This paper is aimed at proving some common fixed point theorems for mappings involving generalized rational-type fuzzy cone-contraction conditions in fuzzy cone metric spaces. Some illustrative examples are presented to support our work. Moreover, as an application, we ensure the existence of a common solution of the Fredholm integral equations: μ τ = ∫ 0 τ Γ τ, v, μ v d v and ν τ = ∫ 0 τ Γ τ, v, ν v d v, for all μ ∈ U, v ∈ 0, η, and 0 < η ∈ ℝ, where U = C 0, η, ℝ is the space of all ℝ -valued continuous functions on the interval 0, η and Γ : 0, η × 0, η × ℝ ⟶ ℝ .